Effects of fibre orientation on tensile properties of ultra high performance fibre reinforced concrete based on meso-scale Monte Carlo simulations. (1st May 2022) - Zhang, Hui; Huang, Yu-jie; Lin, Mo; Yang, Zhen-jun
Abstract: The damage and fracture of ultra high performance fibre reinforced concrete (UHPFRC) is inherently dependent on fibre orientation and distribution. The effects of fibre orientation on the tensile properties of UHPFRC are investigated by meso-scale finite element (FE) simulations. The nonlinear bond-slip behaviour of fibre-mortar interfaces is explicitly modelled by zero-thickness cohesive elements with softening constitutive laws. After validation against existing experiments, extensive Monte Carlo simulations of FE models are conducted with different fibre volume fractions (1.5%, 2.0%, 2.5% and 3.0%) and orientation in the ranges of 0–90° (random), 0–30°, 30–60° and 60–90°, respectively. The fibre orientation is found to significantly influence tensile stress-strain relationships of UHPFRC, fracture patterns in the mortar, stress evolution in the fibres and bond-slip behaviour of the interfaces. Using more fibres is useful only when the fibres are reasonably oriented with respect to the tension direction, and a transition from brittle to ductile failure with strain hardening can be achieved by optimising the fibre orientation even for relatively low fibre content. Empirical equations are curve-fitted between the orientation number and key properties such as the elastic modulus, first-cracking stress and peak stress, which can be used to optimise tensile properties of UHPFRC members.